A Novel Thioredoxin-Dependent Peroxiredoxin (TPx-Q) Plays an Important Role in Defense Against Oxidative Stress and Is a Possible Drug Target in Babesia microti - Zhang, Houshuang; Wang, Zhonghua; Huang, Jingwei; Cao, Jie; Zhou, Yongzhi; Zhou, Jinlin (Frontiers in Veterinary Science, 2020)
Thioredoxin peroxidases (TPxs) are ubiquitous cysteine-based peroxidases that reduce peroxides as part of antioxidant defenses and redox signaling and are essential for Babesia microti protection against adverse environment agents like reactive oxygen species (ROS) and reactive nitrogen species (RNS). To better systematically understand TPxs, we identified a novel 2-Cys peroxiredoxin-Q (BmTPx-Q) of B. microti. The full-length BmTPx-Q gene is 653 bp that consists of an intact open reading frame of 594 bp that encodes a 197-amino acid protein. The predicted protein has a molecular weight of 22.3 kDa and an isoelectric point of 9.18. Moreover, BmTPx-Q showed low identity at the amino acid level to other peroxiredoxins (Prxs) among the currently known subfamilies. The recombinant BmTPx-Q protein (rBmTPx-Q) was expressed in Escherichia coli and purified with beads. The native protein BmTPx-Q was detected using mouse anti-BmTPx-Q polyclonal serum with western blotting and indirect immunofluorescence assay (IFA). In addition, enzyme activity was observed using nicotinamide adenine dinucleotide phosphate (NADPH) as substrate and triggered the NADPH-dependent reduction of the Trx/TrxR system. It was also discovered that BmTPx-Q mainly exists as a monomer whether under its native or functional states. In addition, when incubated with Chloroquine diphosphate salt for 24 h in vitro, the expression of BmTPx-Q showed a marked downward trend with the increase of drug concentration. These results suggest that B. microti uses BmTPx-Q to reduce and detoxify hydrogen peroxides to survive and proliferate inside the host. Furthermore, BmTPx-Q showed the lowest identity with host enzymes and could be a potential drug target for the development of novel strategies to control B. microti infection.